Prediction of Adducts on Positive Mode Electrospray Ionization Mass Spectrometry: Proton/Sodium Selectivity in Methanol Solutions. Issue 5 (October 2015) - Sugimura, Natsuhiko; Furuya, Asami; Yatsu, Takahiro; Shibue, Toshimichi
We used positive mode electrospray ionization (ESI) mass spectrometry to examine 540 in-house high-resolution mass spectrometry (HRMS) samples that formed an adducted positive ion. Of the 540 samples, the sodium adduct ([M + Na] + ) was detected in 480 samples, and the protonated molecule ([M + H] + ) was detected in 92 samples; both [M + Na] + and [M + H] + were detected in 32 samples. No other adduct ions were predominant. The selectivities of these adducts were evaluated by a two-dimensional plot using topological polar surface area (tPSA) and molecular weight. Two predominant trends were observed: [M + H] + converged around tPSA (Å 2 ) = 20 and molecular weight = 250, and the selectivity for [M + Na] + correlated with the tPSA value. These observations were found to be related to the elemental composition of the sample compounds. From the results obtained by positive mode ESI mass spectroscopy under our experimental conditions, predominant trends were observed with respect to adduct selectivity: compounds containing oxygen atom(s) form [M + Na] +, and compounds containing nitrogen but not oxygen atom(s) form [M + H] + . Based on these trends, we developed the "Nitrogen–Oxygen rule" (NO rule) to predict the adduct formed by a given compound on positive mode ESI. This NO rule provides a guideline to estimate elemental composition using ESI-HRMS with methanol as mobile phase.